RARE METALS IN HYDROMINERAL RESOURCES OF ARMENIA AND PERSPECTIVES OF THEIR APPLICATION IN INDUSTRY (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Mineral water resources as additional source for rare metals industry have been discussed in the article. Recovery of rare metals out of thermal, mineral and mine waters with cost-effective ecologic technologies is the main purpose of the paper.
Keywords: rare metals industry; thermal, mineral and mine waters; hydromineral resources of Armenia